Gender Equality and Economic Development: The Role for Information and Communication Technologies - Chen, Derek H. C. (World Bank, Washington, D.C., 2013)
The author focuses on the role that information and communication technologies (ICTs) can play in improving gender equality, so as to enhance long-term economic growth. Employing OLS and IV panel regressions with country fixed-effects, he shows that increases in the level of ICT infrastructure tend to improve gender equality in education and employment. In addition, the author shows that education among the general population is important for improving gender equality. The results provide evidence indicating that gender equality in education is an important contributor to gender equality in employment. Lastly, the results show that economic development tends to lead to some improvements in gender equality in the labor market. Hence, the use of ICTs to improve gender equality in education and employment may initiate a continuous cycle of positive reinforcing feedback effects between gender equality in employment and economic development, leading to further improvements in both.